Arterial stiffness, high fasting glucose, and fatty liver as risk factors for visceral obesity in middle-aged Chinese individuals: a cross-sectional study - Hajime Nawata; Li Ou; Xu Zhang; Qinglan Song; Jing Huang; Jin Hu; Kazue Ito; Shinichi Obo; Takeharu Fukushima; Kaori Iwami; Shizuka Iguchi; Ai Igarashi; et al. (Endocrine Journal)
The prevalence of obesity is increasing rapidly worldwide, particularly in Asia. Visceral obesity, characterized by intra-abdominal fat accumulation, is a precursor to metabolic syndrome, encompassing hyperglycemia, dyslipidemia, and hypertension, which elevate the risk of atherosclerosis and cardiovascular disease. A visceral fat area (VFA) of ≥100 cm2 is a recognized threshold for diagnosing obesity-related metabolic syndrome. This study aimed to identify independent risk factors for VFA ≥100 cm2 in middle-aged Chinese individuals from the general population. We analyzed data from 148 participants (mean age: 49.3 ± 10.8 years; 54% male) who underwent health check-ups. VFA and subcutaneous fat area were assessed using computed tomography, while arterial stiffness and fatty liver were evaluated via brachial-ankle pulse wave velocity (baPWV) and abdominal ultrasonography, respectively. Between-group comparisons (VFA ≥100 cm2 vs. VFA <100 cm2) were conducted using unpaired t-tests and Mann-Whitney U tests, and logistic regression analysis identified risk factors. Multivariable regression analysis revealed that baPWV ≥1,400 cm/s (odds ratio [OR] = 5.71, p = 0.011), waist circumference ≥85 cm (OR = 5.46, p = 0.026), fasting blood glucose (FBG) ≥100 mg/dL (OR = 5.69, p = 0.030), male sex (OR = 12.79, p = 0.029), and fatty liver (OR = 3.99, p = 0.042) were significant independent risk factors for VFA ≥100 cm2. Among these, baPWV ≥1,400 cm/s was the most significant, showing a positive correlation with VFA (r = 0.365, p < 0.001). Visceral obesity (VFA ≥100 cm2) is a critical target for interventions addressing metabolic syndrome, metabolic dysfunction-associated fatty liver disease (MAFLD), and cardiovascular disease, particularly in males.